2020
DOI: 10.1371/journal.pcbi.1007494
|View full text |Cite
|
Sign up to set email alerts
|

Limits on amplifiers of natural selection under death-Birth updating

Abstract: The fixation probability of a single mutant invading a population of residents is among the most widely-studied quantities in evolutionary dynamics. Amplifiers of natural selection are population structures that increase the fixation probability of advantageous mutants, compared to well-mixed populations. Extensive studies have shown that many amplifiers exist for the Birth-death Moran process, some of them substantially increasing the fixation probability or even guaranteeing fixation in the limit of large po… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
73
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(84 citation statements)
references
References 40 publications
4
73
0
1
Order By: Relevance
“…The differences between Birth-death and death-Birth dynamics are major for mutant fixation probabilities, but also in evolutionary game theory, where spatial structure can promote the evolution of cooperation in the latter case, but not in the former [27][28][29]. Previous efforts were made to generalize beyond these dynamics by allowing both types of update to occur in given proportions [30,31]. Interestingly, it was recently shown that no strong or universal amplification of selection can occur when even a small proportion of death-Birth events occurs [31], in contrast to the Birth-death case.…”
Section: Discussionmentioning
confidence: 99%
“…The differences between Birth-death and death-Birth dynamics are major for mutant fixation probabilities, but also in evolutionary game theory, where spatial structure can promote the evolution of cooperation in the latter case, but not in the former [27][28][29]. Previous efforts were made to generalize beyond these dynamics by allowing both types of update to occur in given proportions [30,31]. Interestingly, it was recently shown that no strong or universal amplification of selection can occur when even a small proportion of death-Birth events occurs [31], in contrast to the Birth-death case.…”
Section: Discussionmentioning
confidence: 99%
“…As particles' kinetic energy form temperature, the persistence of opinion enhances the willingness for interaction and forms social temperature [34] , [35] . Supply abundance ensures low social temperature, with a tendency for cooperation and generosity [161] . When access to supplies reaches a critical level, competition for resources replaces cooperation [159] .…”
Section: Definitions Used In the Testmentioning
confidence: 99%
“…Our results suggest that positive environments occur encourage the generosity and cooperation by supporting mental energy growth. Desirable population structures promote cooperation [161] .…”
Section: Thermodynamic Considerations Of Brain Activitiesmentioning
confidence: 99%
“…The six evolutionary dynamics differ in the order in which the birth and death events take place and the stage at which selection occurs. Several dynamics may also be combined into a single mixed dynamics, see, for example, [94,107]. Different updating mechanisms can yield different evolutionary outcomes, see, for example, [101].…”
Section: The Framework Of Broom and Rychtář: The Full Dynamic Modelmentioning
confidence: 99%
“…Similarly, there are some very special directed graphs which act as amplifies (or suppressors) of selection [49] where the structure is critical and small structural changes would make big differences. Amplifying graphs and their properties are discussed in detail in [4,94].…”
Section: Game and Dynamics Parametersmentioning
confidence: 99%